The Relationship between Motivation, Self-efficacy and the Use of Self-Regulatory Strategies: An Investigation of Grade 5 Elementary Students' Literary Knowledge - Lucky Taufik Sutrisno; Erna Susilawati; Yunus Abidin (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
This study aims to investigate the interrelationships between motivation, self-efficacy and the use of self- regulation strategies in relation to grade 5 students' literary knowledge in primary schools. Studying the relationship between motivation, self-efficacy, and the use of self-regulation strategies is important for grade 5 students' literary knowledge because it can have a positive impact on their learning ability and academic achievement. The research method involves collecting primary data through questionnaires given to 100 grade 5 students. The questionnaires are designed to measure students' level of motivation in learning literature, students' self-efficacy regarding their ability to understand and analyze literary works, and students' use of self-regulation strategies in dealing with literary tasks. Correlation analysis will be used to examine the relationships between variables, such as correlation analysis, to explore the relationship between students' motivation, self-efficacy, use of self-regulation strategies, and literary knowledge. The results of this analysis are understanding the interrelationships between motivation, self-efficacy, and the use of self-regulation strategies can help grade 5 students develop a strong interest in literature, increase their confidence in their ability to study literature, and enable them to manage their learning more effectively. This will contribute to increasing their understanding and appreciation of literary works, as well as their overall academic achievement. The findings of this study can provide guidelines for educators in designing effective learning strategies and motivating students in learning literature. This research is also expected to contribute to the field of literature learning research at the primary school level and provide a more comprehensive insight into the factors that influence literary knowledge at this stage.